A Beaver Tale : The Castors of Conners Creek - Wykes, Gerald (Book collections on Project MUSE., 2016)
In A Beaver Tale: The Castors of Conners Creek, author and illustrator Gerald Wykes tells the incredible story of one beaver family's return to the Detroit River in 2008, more than one hundred years after beavers were last seen in the area. Wykes's full-color illustrations and kid-friendly text tell a serious tale of environmental recovery in a fun and accessible way.